Factors affecting conspecific brood parasitism in Wood Ducks Aix sponsa of the intermountain region of western North America - Hafen, Konrad; Koons, David N. (Wildfowl, 2016)
The installation of artificial nest boxes has frequently been used as a management measure to increase breeding habitat and thus bolster Wood Duck Aix sponsa populations. However, Wood Duck populations that rely heavily on nest box programmes are also prone to increased frequency of intense conspecific brood parasitism (CBP), which can reduce egg hatchability and increase rates of nest abandonment among hosts. In 2010, 2012 and 2013 we monitored 95â€“110 nest boxes in northern Utah, USA, for intense CBP (clutches with â‰¥ 16 eggs). Using logistic regression and information-theoretic methods, we compared the influence of nest box visibility, proximity to other nest boxes, and proximity to aquatic habitat on the probability of a Wood Duck nest being intensely parasitized by a conspecific female. Our data indicated that a combination of nest box mount type and wooded habitat cover were the main drivers of intense CBP, with the odds of intense CBP increasing by a factor of 9.0 for boxes mounted on a pole in wooded areas, and by a factor of 20.8 for boxes mounted on a pole in open areas, when these were compared with CBP in boxes mounted on trees in wooded areas. The results agreed with hypotheses that tree-mounted boxes in wooded habitat offer more concealment for nesting females as they enter and leave nests, making their nests less likely to be exploited by prospecting parasites. Placing Wood Duck nest boxes in trees, where possible, might thus decrease the occurrence of intense CBP and the negative impact it can have on the fitness of the host.